2017
DOI: 10.5334/ijic.2491
|View full text |Cite
|
Sign up to set email alerts
|

Why Collaborative Care for Depressed Patients is so Difficult: A Belgian Qualitative Study

Abstract: Although current guidelines recommend collaborative care for severely depressed patients, few patients get adequate treatment. In this study we aimed to identify the thresholds for interdisciplinary collaboration amongst practitioners when treating severely depressed patients. In addition, we aimed to identify specific and feasible steps that may add to improved collaboration amongst first and second level Belgian health care providers when treating depressed patients. In two standard focus groups (n = 8; n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Regardless of the clinical setting, optimal management for patients with MDD who experience R/R requires a multidisciplinary approach. For example, prior studies have demonstrated that collaboration among different healthcare providers benefits patients and can help mitigate relapse and monitor recurrence 19 , 20 . Also beneficial is the administration of symptom-based rating scales to aid in assessing symptom severity and informing treatment adjustments 19 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the clinical setting, optimal management for patients with MDD who experience R/R requires a multidisciplinary approach. For example, prior studies have demonstrated that collaboration among different healthcare providers benefits patients and can help mitigate relapse and monitor recurrence 19 , 20 . Also beneficial is the administration of symptom-based rating scales to aid in assessing symptom severity and informing treatment adjustments 19 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties, however, are encountered when complex models such as these are integrated into clinical practice [ 12 , 13 ]. Our team designed and implemented a strategy for the widescale implementation of a multicomponent collaborative care program (INDI) designed to improve the management of depression in primary care centers within the Catalan public health system [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The substantial amount of resources utilized to facilitate implementation, ranging from $208,314 to $236,263 per network excluding travel cost, is not surprising given the complexity of PCMHI [1,6,13], the difficulty of changing the structure and processes of care [15,39,40], the large number of contextual barriers that can hinder implementation [10,12,15,16,19], and the number of stakeholders that might need to be involved. Our study findings support the need to protect time for stakeholder participation in facilitation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Models of primary care mental health integration (PCMHI) are complex and challenging to implement, requiring change in the structure and processes of care delivery [2,6,10,11]; provider values, attitudes, roles, and skills [1,3,6,12,13]; and organizational culture [6,14,15], including ways of working together [6,12]. Further, primary care settings and their capacity for change vary widely [1,[14][15][16][17][18][19]. Thus, such programs and the implementation process must be tailored to the needs and resources of the organizational context and PCMHI stakeholders, e.g., leaders, providers, and other staff [10,17].…”
Section: Introductionmentioning
confidence: 99%